Teacher Performance in Terms of the Aspects of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence - Lie, Darwin; Simatupang, Sudung; Harini, Sri; Dharma, Edy; Sudirman, Acai (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aimed to analyze the role of intellectual intelligence, emotional intelligence and spiritual intelligence in affecting the teacher performance. This study used a research design of an associative quantitative approach. The data were collected through documentation and online questionnaires. This study used a sample of 39 respondents with the determination of the sample size using the saturated sample formula. Partial least square was applied to examine the relationship between teacher performance, intellectual intelligence, emotional intelligence and spiritual intelligence. The results of this study showed that of the three hypotheses formulated, there were two hypotheses that were rejected. For the effect of the intellectual intelligence variable on the teacher performance variable, the results did not have a significant effect, and then, the effect of the emotional intelligence variable on the teacher performance variable was the same, which was not affected significantly. Meanwhile, the spiritual intelligence variable had a significant effect on teacher performance.